Anti-ophidian activity of Bredemeyera floribunda Willd. (Polygalaceae) root extract on the local effects induced by Bothrops jararacussu venom - Alves, Natacha Teresa Queiroz (2019)
Bredemeyera floribunda roots are popularly used to treat snakebites in the semiarid region of Northeast Brazil, and previous studies indicate the anti-ophidian actions of triterpenoid saponins found in its roots. To assess B. floribunda root extract (BFRE) activity against the effects of Bothrops jararacussu venom (BjuV), antiphospholipasic, antiproteolytic, antihemorrhagic, antinecrotic, and anti-edematogenic activities were investigated in mice. Phytochemical analysis revealed the presence of saponins, flavonoids, and sugars, with rutin and saccharose being the major constituents of BFRE. Acute toxicity was determined and BFRE was nontoxic to mice. Phospholipase A2 and proteolytic activities induced by BjuV were inhibited in vitro by BFRE at all concentrations tested herein. BFRE (150 mg/kg) inhibited paw edema induced by BjuV (50 mg/animal), reducing total edema calculated by area under the curve, but carrageenan-induced paw edema was unchanged. Hemorrhagic and necrotizing actions of BjuV (50 mg/animal) were considerably decreased by BFRE treatment. Thus, BFRE blocked the toxic actions of B. jararacussu venom despite having no anti-inflammatory activity, which points to a direct inhibition of venom’s toxins, as demonstrated in the in vitro assays. The larger amounts of rutin found in BFRE may play a role in this inhibition, since 30,40-OH flavonoids are known inhibitors of phospholipases A2.